Korpora in Lehre und Forschung - Anstein, Stefanie (bu,press, 2011)
Today, the teaching of knowledge is facing a twofold challenge: the demand for comprehensibility despite the high complexity of contents and the achievement of acceptable results in school in situations of ever-growing diversity. This opens up new research areas for linguistics: on the one hand, the communicative acts of members of a language community in everyday life and in specialized settings; on the other hand, the variable contexts of the speech acts, which require the co-orientation of social actors, which in turn also needs to be acquired and practiced like the languages with their formal and structural characteristics. Based upon these premises, this volume presents findings and theoretical approaches which make corpus findings available for the study and the didactics of language teaching concerning the the three school languages ??of German, Italian and English. Special emphasis is put on the varieties of the German language in South Tyrol and the interface problem.